2002
DOI: 10.1042/cs20010135
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of brachial artery mean 24 h pulse pressure in individuals with Type II diabetes mellitus and untreated mild hypertension

Abstract: Brachial artery pulse pressure is a predictor of (cardiovascular) morbidity, but its determinants in individuals with Type II diabetes and untreated mild hypertension have not been elucidated. We therefore cross-sectionally investigated determinants of brachial artery mean 24 h pulse pressure in 60 individuals (40 males; age, mean +/- S.D., 57.8 +/- 7.5 years) with Type II diabetes [median diabetes duration (interquartile range), 6.3 (3.6-10.1) years] and untreated mild hypertension [sitting blood pressure >14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…22 In a recent report, based on a small number of patients with type 2 diabetes, PP was related to albumin excretion. 23 The present study showed that office PP correlated with albumin excretion within the normoalbuminuric range. In this study we also found that patients in the higher office PP quartiles were characterized by the more pronounced albumin/ creatinine ratio.…”
Section: Discussionsupporting
confidence: 62%
“…22 In a recent report, based on a small number of patients with type 2 diabetes, PP was related to albumin excretion. 23 The present study showed that office PP correlated with albumin excretion within the normoalbuminuric range. In this study we also found that patients in the higher office PP quartiles were characterized by the more pronounced albumin/ creatinine ratio.…”
Section: Discussionsupporting
confidence: 62%
“…3 We then determined the average time delay (mean of 3 recordings of 4 seconds per artery) from the electrocardiograph trigger to 10% of the ascending slope of the distension curve of both arteries and subtracted the carotid value from the femoral value to obtain the carotid-femoral transit time. 14 Reproducibilities of the time-decay method, carotid pulse pressure, augmentation index, and carotid-femoral transit time have been reported. 3,14 …”
Section: Carotid-femoral Transit Timementioning
confidence: 99%
“…14 Reproducibilities of the time-decay method, carotid pulse pressure, augmentation index, and carotid-femoral transit time have been reported. 3,14 …”
Section: Carotid-femoral Transit Timementioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Briefly, we measured distensibility and compliance of the carotid, the femoral and the brachial arteries, Young's elastic modulus of the carotid artery and total systemic arterial compliance. These measurements were performed by use of an ultrasound scanner (Pie350 scanner, (linear array, 7.5 MHz transducer), Pie Medical BV, Maastricht, The Netherlands) that was connected to a PC equipped with vessel wall movement detection software and an acquisition system (Wall Track System, Pie Medical).…”
Section: Arterial Stiffnessmentioning
confidence: 99%